Elicitin-Induced Distal Systemic Resistance in Plants is Mediated Through the Protein–Protein Interactions Influenced by Selected Lysine Residues - Uhlíková, Hana; Obořil, Michal; Klempová, Jitka; Šedo, Ondrej; Zdráhal, Zbyněk; Kašparovský, Tomáš; Skládal, Petr; Lochman, Jan (Frontiers in Plant Science, 2016)
Elicitins are a family of small proteins with sterol-binding activity that are secreted by Phytophthora and Pythium spp. classified as oomycete PAMPs. Although alfa- and beta-elicitins bind with the same affinity to one high affinity binding site on the plasma membrane, beta-elicitins (possessing 6-7 lysine residues) are generally 50- to 100-fold more active at inducing distal HR and systemic resistance than the alfa-isoforms (with only 1-3 lysine residues). To examine the role of lysine residues in elicitin biological activity, we employed site-directed mutagenesis to prepare a series of beta-elicitin cryptogein variants with mutations on specific lysine residues. In contrast to direct infiltration of protein into leaves, application to the stem revealed a rough correlation between protein’s charge and biological activity, resulting in protection against Phytophthora parasitica. A detailed analysis of proteins’ movement in plants showed no substantial differences in distribution through phloem indicating differences in consequent apoplastic or symplastic transport. In this process, an important role of homodimer formation together with the ability to form a heterodimer with potential partner represented by endogenous plants LTPs is suggested. Our work demonstrates a key role of selected lysine residues in these interactions and stresses the importance of processes preceding elicitin recognition responsible for induction of distal systemic resistance.